Avaliação tecnológica da substituição do óleo de palma em gelados comestíveis - Munhoz, Clarissa da Silva (Universidade Federal de São Carlos, 2023)
This study aimed to test three lipid sources to replace palm oil in ice cream. The standard formulation (PAD) was composed of 6.5% of palm oil, 62.54% of water, 11% of glucose syrup, 11% of sugar, 6.5% of whey protein, 1.7% of skimmed milk powder, 0,65% of mix of stabilizers and emulsifiers, and 0.014% of annatto coloring. The other treatments differed from the PAD sample by the origin of the lipid source, where prototype 01 (PT1) used 6.5% of the blend of soybean fat, fully hydrogenated palm oil and palm stearin, prototype 02 (PT2) with 6,5% of coconut oil and prototype 03 (PT3) used 6,5% of the blend of shea oil and refined palm oil. The samples were submitted to analyses of rheology, air incorporation (overrun) and melting behavior, in order to evaluate the influence of these substitutions on their rheological, physical and stability characteristics. Based on the rheograms, the mixes showed a pseudoplastic behavior ant the PT3 and PAD samples showed the highest apparent viscosity values. With regard to the air incorporation and stability analyses, the PT1 exhibited the lowest overrun and the highest melting rate, as both parameters tend to be inversely related. Samples PT2 and PT3 presented intermediate results for overrun and melting behavior, being, therefore, possible alternatives to replace palm oil, the lipid source that presented the best technological results in the present work.
Technological evaluation of the replacement of palm oil in ice cream
Keywords: Blend de óleos; Elaeis guineensis; Derretimento; Óleo de coco; Overrun; Sorvete; Blends of oils; Elaeis guineensis; Melting; Coconut oil; Ice cream; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS